Poor glycemic control might compromise the efficacy of chemotherapy in non‐small cell lung cancer patients with diabetes mellitus. (12th December 2019) - Zeng, Xianghua; Xu, Cheng; Cheng, Jianan; Sun, Chengdu; Wang, Zhongyu; Gong, Zhihua; Long, Haixia; Zhu, Bo
Abstract: Background: Previous studies indicated that type 2 diabetes mellitus (T2DM) is related to an increased lung cancer risk, but its role in the prognosis of NSCLC remains conflicting. This study investigated the impact of blood glucose control on the outcomes in NSCLC patients with T2DM treated with platinum‐based doublets. Methods: Clinicopathological and survival data from 191 T2DM patients with advanced NSCLC, who received platinum‐based chemotherapy, were retrospectively analyzed. Based on the blood glucose conditions during chemotherapy, patients were classified into poor (n = 84) and good control (n = 107) groups. Progression‐free survival (PFS) was assessed using the Kaplan‐Meier method. Results: The median PFS among patients with good glycemic control [197.0 (95% CI: 136.3‐257.7) days] was longer than that among those with poor control [132.0 (95% CI: 112.5‐151.5) days] ( P = .0003). Further subgroup analysis of lung squamous carcinoma and adenocarcinoma patients showed that the median PFS of the good control group was also significantly longer than that of the poor control group [179.0 (95% CI: 78.4‐279.6) days vs 125.0 (95% CI: 110.9‐139.1) days, P = .0014; 197.0 (95% CI: 124.3‐269.7) days vs 154.0 (95% CI: 129.9‐178.1) days, P = .0359; respectively]. The incidence rates of side effects were similar among patients with good glycemic control and those with poor glycemic control (all P > .05). Conclusions: Satisfactory glycemic control during platinum‐based chemotherapy might provide a survival benefit to T2DM patients with NSCLC. Further studies are warranted to confirm our findings. Abstract : In non‐small cell lung cancer patients with type 2 diabetes mellitus, poor glycemic control may lower the efficacy of platinum‐based chemotherapy due to the shorter progression‐free survival, and so it is much important to strengthen glycemic control in these patients.